DIGITAL LITERACY, ENTREPRENEURIAL ORIENTATION, AND ACCESS TO FINANCING: FACTORS AFFECTING BUSINESS INNOVATION AND COMPETITIVE ADVANTAGE IN INDONESIAN MSMES - Lasmiatun, KMT; Zulfikri , Agung (Gapenas Publisher, 2025)
This study investigates the influence of digital literacy, entrepreneurial orientation, and access to financing on business innovation and competitive advantage among micro, small, and medium enterprises (MSMEs) in Indonesia. Using a quantitative approach, data were collected from 180 MSME owners and managers through a structured questionnaire with a five-point Likert scale. Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) was employed to test the hypothesized relationships. The results indicate that digital literacy, entrepreneurial orientation, and access to financing significantly enhance business innovation, which in turn positively affects competitive advantage. Moreover, business innovation partially mediates the relationship between the independent variables and competitive advantage, highlighting its critical role as a mechanism linking resources and capabilities to firm performance. The findings underscore the importance of developing digital skills, fostering entrepreneurial behavior, and improving financial accessibility to strengthen the innovation capacity and competitiveness of Indonesian MSMEs.